PEMBUATAN DAN UJI MUTU FISIK KRIM EKSTRAK HERBA PEGAGAN (Centella asiatica) (L.) - dzulasfi; Suhartini; Agha Izha Fahiza (Jurnal Kesehatan Yamasi Makassar, 2023)
This study aims to make and test the Physical Quality Test of Centtella asiatica (L) extract of Centtella asiatica (L) in cream dosage forms with 0.5% and 1% extract concentrations. The type of research carried out is a laboratory experimental research by making Centella asiatica (L) herbal cream and testing the physical quality of the cream by conducting organoleptic, homogeneity, pH and dispersibility tests. The results of the observation of the pH test at a concentration of 0.5% is 6.13, a concentration of 1% is 6.47 while the dispersion test at a concentration of 0.5% is 5.1 cm, and a concentration of 1% is 5.2 cm. The results of the research on making and testing the physical quality of the cream of gotu kola herb extract 0.5% and 1% met the requirements for the physical quality test of cream preparations.